Comparison of Physical Fitness between Rural and Urban Students in Bardiya District - Bohara, Kishore; Chiluwal, Shailandra; Thapa, Suresh Bahadur (Journal of Durgalaxmi, 2025)
This study examines the physical fitness of rural and urban students in the Bardiya district. A sedentary lifestyle has frequently been prompted by automation and technological progress, leading to hypokinetic disorders that impact global health. Physical fitness is characterized by an individual's capacity to do daily tasks effectively and efficiently; it involves various health-related components, including cardiovascular endurance, muscular strength, flexibility, and body composition. The present study employed a quantitative descriptive research method, assessing 80 secondary school boys with the AAHPER (American Association for Health, Physical and Recreation) Youth Fitness Test Battery, comprising 40 rural and 40 urban participants. Statistical analysis (T-test) revealed that rural pupils excel greatly in several physical fitness assessments, including pull-ups, knee bent sit-ups, standing broad jump, and endurance, due to their superior muscular and cardiovascular development. No notable changes were detected in the 50-yard dash between the two groups. The findings further substantiate the necessity of enhancing physical activity among urban populations to bridge the fitness gap and advocate for more participation in sports and exercise inside schools, particularly to alleviate the adverse effects of sedentary lives among urban adolescents.